The Effect of Average Collection Period, The Inventory Turnover Period, and The Average Inventory Period on Return on Assets - Hamad, Samer (European Scientific Journal, ESJ, 2024)
The importance of the Cash Conversion Cycle (CCC) emerges in helping to make appropriate financing decisions for different industries. Therefore, the research focuses on the return on assets (ROA) issues and how it is affected by the three components of the cash conversion cycle; Average Collection Period (ACP), Average Inventory Turnover Period (ITP), and Average Payment Period (APP). Since the topic refers to the potential statistical relationship between the three components and the return on assets, the research has been organized to find the validity of the answer to the research questions and hypothesis on how components affect the return on assets. Statistical analysis reveals a positive relationship between APP and ROA, showing that longer payment periods allow companies to retain cash, thereby increasing asset profitability. Conversely, negative correlations between ACP, ITP, and ROA suggest that shorter collection and turnover periods contribute to higher asset returns by minimizing cash tied up in receivables and inventory and reducing holding costs. The research’s findings underline the importance of strategic CCC management, encouraging managers to extend APP when possible while reducing ACP and ITP, to enhance liquidity, maximize asset performance, and prevent financial distress.